Education and Human Capital Externalities: Evidence from Colonial Benin * - Wantchekon, Leonard; Klašnja, Marko; Novta, Natalija (Quarterly Journal of Economics, 2015)
Abstract Using a unique data set on students from the first regional schools in colonial Benin, we investigate the effect of education on living standards, occupation, and political participation. Since both school locations and student cohorts were selected with very little information, treatment and control groups are balanced on observables. We can therefore estimate the effect of education by comparing the treated to the untreated living in the same village, as well as those living in villages where no schools were set up. We find a significant positive treatment effect of education for the first generation of students, as well as their descendants: they have higher living standards, are less likely to be farmers, and are more likely to be politically active. We find large village-level externalities—descendants of the uneducated in villages with schools do better than those in control villages. We also find extended family externalities—nephews and nieces directly benefit from their uncle’s education—and show that this represents a “family tax,” as educated uncles transfer resources to the extended family.